PEMANFAATAN KREDIT KONSUMTIF OLEH MASYARAKAT (STUDI KASUS DI DESA PULAU JAMBU KECAMATAN KUOK KABUPATEN KAMPAR) - Purwasih, Ratih; ", Yoserizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study to find out why the people prefer to take advantage of consumer credit andfurther to determine the factors that cause the public to use the credit facility, in this case theresearchers examined the existing communities in the villages of the Pulau Jambu Villagewith the total households as 2893, they got the facility of credits from the stands amount 6stands, while the amount of credit users in the stand as 643 people. Sampling technique thatuses is proposive sampling with the sample of 60 people with quantitative deskriptif analys,the tools used in this study is a questionnaire, interviews and documentation, the theory thatused in this study is the social exchange theory from Homans. The research looked at humansas beings who have various needs, and rarely encountered problems in repayment ofconsumer credit, which affects their income to their behavior in the repayment of loans, therespondents gave a good response to credit traders that look of this study increased the valueof a community perceives the benefits merchant credit, see the ease and drought provided bythe creditor to the consumers or customers, as beings who are never satisfied, they have avariety of ways to meet the satisfaction or desire, as well as the use of credit fasilitar, is theone way to meet their needs or desires goods or household products and others, than for theneeds and survival.Keywords: Credit Utilization,. Consumptive Patterns